Human Immune System Diseasome Networks and Female Oviductal Microenvironment: New Horizons to be Discovered - Taraschi, Angela; Cimini, Costanza; Colosimo, Alessia; Ramal-Sanchez, Marina; Moussa, Fadl; Mokh, Samia; Valbonetti, Luca; Capacchietti, Giulia; Tagaram, Israiel; Bernabò, Nicola; Barboni, Barbara (Frontiers in Genetics, 2022)
Human hypofertility and infertility are two worldwide conditions experiencing nowadays an alarming increase due to a complex ensemble of events. The immune system has been suggested as one of the responsible for some of the etiopathogenic mechanisms involved in these conditions. To shed some light into the strong correlation between the reproductive and immune system, here we built a network using a useful bioinformatic tool (DisGeNET), in which the key genes involved in the sperm-oviduct interaction were linked. This constitutes an important event related with Human fertility since this interaction, and specially the spermatozoa, represents a not-self entity immunotolerated by the female. As a result, we discovered that some proteins involved in the sperm-oviduct interaction are implicated in several immune system diseases while, at the same time, some immune system diseases could interfere by using different pathways with the reproduction process. The data presented here could be of great importance to understand the involvement of the immune system in fertility reduction in Humans, setting the basis for near immune therapeutic tools.